Studi Kimia Fisik Fluida pada Manifestasi Panas Bumi Danau Linow - Vincensius Jamlean; Cyrke A. N. Bujung; Alfrie M. Rampengan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Lake Linow is one of the volcanic lakes that has geothermal activity characterized by geothermal manifestations in the form of hot springs that appear on the surface. The purpose of this research is to study the type of fluid and estimate the reservoir temperature. The methods used in this research are ion analysis of fluid content using spectrometry, pH, and physical analysis of fluids in the form of physical appearance manifestations of hot springs. The results showed that the hot springs in Lake Linow are immature water types with a high percentage of Mg concentration. It is interpreted that there is a process of dilution with other elements and mixing with meteoric water which is rich in Mg elements. Calculations using water geothermometer equations on hot spring samples in the area are estimated to have a reservoir temperature of 92.85°C-127.9°C